Logistic and international fruticulture trade in the state of Minas Gerais – Brazil - Oliveira, Igor Martins; Pereira, Luiz Andrei Gonçalves (Geografares, 2019)
In the era of globalization, the world economy has undergone a process of productive restructuring, intensifying flows in the territories inherent to the spatial interactions of resources, goods and services that circulate between national and international markets. The objective of this work is to analyze the sociospatial dynamics of the international trade flows of the state of Minas Gerais through the logistics of import and export fruit networks, from 2000 to 2017. As a result, it was identified that in the market Minas Gerais has a commercial relationship with 88 countries, 52 in export networks and 36 in the import network. In the operationalization of flows in global trade, transport logistics was carried out through the road, sea and air modalities, being configured as a geographic element, since commercial transactions demand the management of the fluidity, planning and organization of the different territories.